2005
DOI: 10.1002/ijc.20840
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a rat model with site‐specific bone metastasis induced by MDA‐MB‐231 breast cancer cells and its application to the effects of an antibody against bone sialoprotein

Abstract: Metastasis into the skeleton is a serious complication of certain neoplastic diseases such as breast, prostate and lung cancer, but the reasons for this osteotropism are poorly understood. Our aim was to establish a physiologically relevant animal model that is characterized by osteolytic lesions confined to the hind leg of nude rats. For this purpose, we injected 1310 5 MDA-MB-231 human breast cancer cells transfected with GFP into the superficial epigastric artery, which is an anastomosing vessel between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 32 publications
(28 reference statements)
0
82
0
Order By: Relevance
“…16,31 To investigate metastatic bone cancer, MDA-MB231 human breast cancer cells (5 × 10 5 in 1 ml) were injected into the femoral arteries of nude rats. 12 Osteolytic lesions occurred exclusively in the femur, tibia, and fibula of these animals, and if the tumor cells were preincubated with an antibody against bone sialoprotein, osteolytic lesion size was reduced significantly. In contrast, R3327 prostate cancer cells were injected directly into the left cardiac ventricle, intravenously, or intraosseously into male Copenhagen rats for observation of metastatic lesions and their relationship to pain.…”
Section: Models Of Cancer Painmentioning
confidence: 87%
“…16,31 To investigate metastatic bone cancer, MDA-MB231 human breast cancer cells (5 × 10 5 in 1 ml) were injected into the femoral arteries of nude rats. 12 Osteolytic lesions occurred exclusively in the femur, tibia, and fibula of these animals, and if the tumor cells were preincubated with an antibody against bone sialoprotein, osteolytic lesion size was reduced significantly. In contrast, R3327 prostate cancer cells were injected directly into the left cardiac ventricle, intravenously, or intraosseously into male Copenhagen rats for observation of metastatic lesions and their relationship to pain.…”
Section: Models Of Cancer Painmentioning
confidence: 87%
“…Among various options that can be envisaged the combination with an agent targeting the pathophysiology of skeletal lesions seems therapeutically attractive. In addition to these studies demonstrating that an IgY-antibody against BSPII was effective in reducing proliferation, colony formation and migration of MDA-MB-231 GFP+ cells in vitro as well as in vivo it could be shown that this treatment induced new bone formation in the aforementioned nude rat model (34,35). Therefore it was the aim of this study to combine a potent bisphosphonate, e.g., zoledronic acid, with the IgY antibody for treating the mammary carcinoma cell line MDA-MB 231 GFP+ , which causes osteolytic lesions in vivo.…”
Section: Combination Treatment Of Lytic Skeletal Metastasis With the mentioning
confidence: 91%
“…For all procedures, rats were anesthetized using a mixture of nitrous oxide (1 l/min), oxygen (0.5 l/min) and isoflurane (1.5 vol%). MDA-MB-231 cells (10 5 ) were injected into the right superficial epigastric artery as described previously (24). Resulting bone metastases were observed exclusively in the femur, tibia and fibula of the right hind leg.…”
Section: Animal Model and Treatment Applicationmentioning
confidence: 99%